2014
DOI: 10.1016/j.egypro.2014.10.116
|View full text |Cite
|
Sign up to set email alerts
|

Solar Energy Resource Assessment of the Geba Catchment, Northern Ethiopia

Abstract: The global shift towards renewable energy is manifested in developing countries such as Ethiopia primarily because of continuous economic growth in the last two decades and secondly due to the vast untapped potential resources. In addition to other factors, the lack of accurate data of the resources has, however, hampered the development of solar energy technologies. The aim of this paper is to investigate the resource estimation by undertaking direct measurements at selected sites in the Northern part of Ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The decrease in transmittance with increasing particle concentration in GO nanofluids can be attributed to the particle's scattering and absorption of light, multiple scattering effects, aggregation and clustering of particles, and the unique light‐matter interactions of graphene oxide nanoparticles. These factors lead to increased scattering, absorption, and light trapping within the nanofluid, reducing transmittance 23 . However, it has been reported that the behavior is not always linear since, at some points, they can appear as non‐linear, which could explain why the GO presents practically the same transmittance at the 370 nm peak for the 200 and 500 ppm, although it can also be attributed to equipment measurement errors or non‐homogeneous dispersion of the nanoparticles in the fluid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in transmittance with increasing particle concentration in GO nanofluids can be attributed to the particle's scattering and absorption of light, multiple scattering effects, aggregation and clustering of particles, and the unique light‐matter interactions of graphene oxide nanoparticles. These factors lead to increased scattering, absorption, and light trapping within the nanofluid, reducing transmittance 23 . However, it has been reported that the behavior is not always linear since, at some points, they can appear as non‐linear, which could explain why the GO presents practically the same transmittance at the 370 nm peak for the 200 and 500 ppm, although it can also be attributed to equipment measurement errors or non‐homogeneous dispersion of the nanoparticles in the fluid.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the transmittance in the visible spectrum (380-750 nm) is low, the range where the sun delivers the most energy at the studied wavelengths. 23 However, it has been reported that the behavior is not always linear since, at some points, they can appear as non-linear, which could explain why the GO presents practically the same transmittance at the 370 nm peak for the 200 and 500 ppm, although it can also be attributed to equipment measurement errors or nonhomogeneous dispersion of the nanoparticles in the fluid. Still, the latter does not take much force because of the good stability of the nanofluid.…”
Section: Transmittancementioning
confidence: 99%
“…1 ). The catchment covers an area of nearly 5133 km 2 with a mean elevation of 2164 m above sea level (elevation varies from 955 to 3295 m) [ 1 , 2 ]. The catchment is extensively cultivated and agricultural activities occur even on many of the steep and stony valley sides [3] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…This will increase the efficiency of the solar collector by 15 percent (Satcunanathan and Deonarine, 1973). Therefore, the peak net heat flux collected from the available 5.59 ℎ −1 −2 will be 918 −2 (Mahmud et al, 2014). The outlet was a pressure outlet with gauge pressure of 0 Pa.…”
Section: Boundary Conditionsmentioning
confidence: 99%